BRINGING OUT OF TOPICAL STUDY DIRECTIONS IN PROCUREMENT MANAGEMENT OF MANUFACTURING COMPANY ON BOTH NATIONAL AND INTERNATIONAL LEVELS - K. Erygin (Вестник университета)
In the article the specificity of procurement management organization of a manufacturing firm is spotlighted, considered the range of topical study directions in this sphere and their perspectives.